Looking after that Sign which is like Man: C. S. Peirce’s Philosophical Semiotics and the Transdisciplinar Practice of Knowledge (Nóema, 2024)
The main purpose of this article is to explore a hermeneutical reading of C. S. Peirce Semiotics. It will be the effort to track down the main themes in common between the transdiciplinar approach to the scientific research and the ‘Pragmaticistic’ method of inquiry. More than being a way of obtaining a trustworthy method, Semiotics may be well considered as a philosophical experience of the world. In this perspective Peirce’s thought is a precious index to remark the transdiciplinar instances, but also to question the isolation between different disciplines. Not a matter of explaining and giving foundation to a system free from imperfections, nor an account to make our knowledge’s limitations more functional and less disturbing. Instead, facing critically the accomplished roots we share with our historical grounding, made of difficult words, will be the work of a real philosophical Hermeneutics, as it was for Peirce’s Pragmaticism.
Keywords: Phenomenology; Experience; Continuity; Struggle; Self-referentiality; Finiteness; Duality; Pragmaticism; Coscience; Doubt